Through dialogue of cultures and convergence of civilizations – modern China on the partnership road towards development, peace and future of humanity: (Sociological marginalia about the Chinese strategy “Belt and Road”) - Mitrović, Ljubiša (Napredak, 2024)
The paper elaborates on the following Chinese strategy: the dialogue of cultures and convergence of civilizations are a road of achieving partnership for sustainable development and peace in the world. The author first gives an overview of the history of Chinese culture and civilization: its depth, breadth and giant accomplishments. Then he discusses modern China from the period after Mao’s death and its leaders/reformers, in particular Deng Xiaoping and Xi Jinping, as the founders of the new development strategy in China’s internal and foreign politics. In that context, the focus of the author’s analysis is on China’s modernization and development strategy, relying on the rapid and high development of education, science and advanced technologies of the third and fourth developmental-civilizational waves, as well as liberalization of economy and democratization of social and political relations; the “Belt and Road” strategy – i.e., China’s great opening up and cooperating with the world through partnership for the sake of universal wellbeing of humanity, globalization with a human face, multipolar order and peace in the world.